Avaliação dos recursos humanos/econômicos da área Centro-Oeste do Rio Grande do Sul - Bezzi, Meri Lourdes; Hahn, Wanderlei (Geografia Ensino & Pesquisa, 2016)
Avaliação dos recursos humanos/econômicos da área Centro-Oeste do Rio Grande do Sul